Implementasi Peraturan Daerah Nomor 2 Tahun 2012 Tentang Pengawasan, Pengendalian, Pengedaran dan Pelarangan Penjualan Minuman Beralkohol di Kabupaten Bantul - Nareswari Kencana (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2019)
Abstract.The implementation of the law takes place because of a violation of law. In this case the law that has been violated must be enforced. It is through this law enforcement that the law becomes a reality. Bantul Regency is a district in the Special Region of Yogyakarta which is also an international tourism destination. One of the regional income is obtained from the tourism sector, then indirectly the culture and also the needs of tourists will enter the area. So to regulate the circulation of alcoholic beverages in Bantul Regency Regional Regulation No. 2 of 2012 was formed, but until now law enforcement on the circulation and sale of alcoholic beverages is still experiencing problems. Some laws and regulations that regulate the circulation and sale of alcoholic beverages, allow the Regional Government to take steps in accordance with the conditions of their respective regions, while still taking into account the applicable laws and regulations.Keywords: Alcoholic Beverages, Regional Regulations, Bantul Abstrak. Pelaksanaan hukum berlangsung karena pelanggaran hukum.Dalam hal ini hukum yang telah dilanggar itu harus ditegakkan. Melalui penegakan hukum inilah hukum menjadi kenyataan. Kabupaten Bantul merupakan suatu kabupaten di Daerah Istimewa Yogyakarta yang juga merupakan destinasi pariwisata Internasional. Pendapatan daerah didapatkan salah satunya dari sektor pariwisata tersebut, maka secara tidak langsung budaya dan juga kebutuhan para wisatawan akan masuk ke dalam daerah. Maka untuk mengatur peredaran minuman beralkohol di Kabupaten Bantul dibentuklah Peraturan Daerah Nomor 2 Tahun 2012, namun sampai saat ini penegakan hukum terhadap pengedaran dan penjualanminuman beralkohol masih mengalami kendala.Beberapa peraturan perundang-undangan yangmengatur pengedaran dan penjualan minuman beralkohol, memungkinkanPemerintah Daerah untuk mengambil langkah sesuai kondisi daerah masing-masing,dengan tetap memperhatikan peraturan perundang-undangan yang berlaku.Kata Kunci: Minuman Beralkohol, Peraturan Daerah, Bantul